Surface shortwave cloud radiative effect of cumulus and stratocumulus-cumulus cloud types in the Caribbean area (Camagüey Cuba, 2010-2016) - Barja Gonzalez, Boris; Rosas, Jorge; Cachorro, Victoria Eugenia; Toledano, Carlos; Antuña-Marrero, Juan Carlos; Estevan, Rene; Frutos, Ángel de (My University, 2023)
ABSTRACT The effects of cumulus (Cu) clouds and the combination of stratocumulus-cumulus (Sc-Cu) clouds on solar radiation at the Earth's surface were evaluated at Camagüey, Cuba, during a 6-yr period (from June 2010 to May 2016). Two methods to calculate the cloud radiative effect (CRE) were employed. The first method (CREm) uses solar irradiances in cloudy conditions from actinometric observations, where cloud information was also reported by visual observation. In the second method (CRE0) surface solar irradiances were estimated for both cloudy and clear sky conditions using a 1-D radiative transfer model, and cloud optical depth (COD) retrieved from an AERONET sun-photometer as the main input. A temporal correspondence criterion between COD retrievals and actinometric observations was performed in order to classify the COD of each cloud type. After the application of this criterion, the COD belonging to the optically thin clouds was removed. Finally, 255 and 732 COD observations for Cu and Sc-Cu, respectively, were found. Results show a statistically significant difference at the 95% confidence level between CRE calculated for Sc-Cu and Cu, using both methods. Mean values of CREm and CRE0 for Cu (Sc-Cu) were −442 (−390) and −460 (−417) Wm-2, respectively. CRE0 shows a linear relation with ln(COD), with stronger correlation at a lower solar zenith angle. The shortwave cloud effect efficiency (CEE) for the two cloud types sharply decreases with the increase of the COD value up to 20. For larger COD, the CEE is less sensitive to the increase of COD.
Keywords: cloud effects on solar radiation (cre) at surface; cloud optical depth (cod); cumulus and stratocumulus; cloud effect efficiency (cee)